2005
DOI: 10.1002/jcp.20444
|View full text |Cite
|
Sign up to set email alerts
|

A critical overview of ESEM applications in the biological field

Abstract: Scanning Electron Microscope (SEM) is a powerful research tool, but since it requires high vacuum conditions, the wet materials and biological samples must undergo a complex preparation that limits the application of SEM on this kind of specimen and often causes the introduction of artifacts. The introduction of Environmental Scanning Electron Microscope (ESEM), working in gaseous atmosphere, represented a new perspective in biological research. Despite the fact that many biological applications have demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
116
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(134 citation statements)
references
References 32 publications
0
116
0
10
Order By: Relevance
“…After fixation, the samples were rinsed twice with distilled water to avoid salt precipitation, and observed using a FEI-Quanta 200 Scanning Electron Microscope (Hillsboro, OR, USA) equipped with a gaseous secondary electron detector (GSED) under specific conditions: 12.5 kV, a spot size of 5-6, 5 torr vacuum, 2500× magnification and a 6 mm working distance. To avoid the collapse of cells, a pump-down routine of four cycles of 5/10 torr, finishing at 5 torr, was carried out for a specimen cooled to 3 • C (Muscariello et al, 2005). Image analysis was performed with ImageJ 1.42 (NIH, Bethesda, MD, USA), and the following parameters were evaluated: cellular shape was determined by area measurement and maximum Feret's diameter (maximum caliper length); the solidity of cells was estimated by the ratio of the area of a cell to the area of its convex hull (Peterbauer et al, 2011).…”
Section: Environmental Scanning Electron Microscopy (E-sem)mentioning
confidence: 99%
“…After fixation, the samples were rinsed twice with distilled water to avoid salt precipitation, and observed using a FEI-Quanta 200 Scanning Electron Microscope (Hillsboro, OR, USA) equipped with a gaseous secondary electron detector (GSED) under specific conditions: 12.5 kV, a spot size of 5-6, 5 torr vacuum, 2500× magnification and a 6 mm working distance. To avoid the collapse of cells, a pump-down routine of four cycles of 5/10 torr, finishing at 5 torr, was carried out for a specimen cooled to 3 • C (Muscariello et al, 2005). Image analysis was performed with ImageJ 1.42 (NIH, Bethesda, MD, USA), and the following parameters were evaluated: cellular shape was determined by area measurement and maximum Feret's diameter (maximum caliper length); the solidity of cells was estimated by the ratio of the area of a cell to the area of its convex hull (Peterbauer et al, 2011).…”
Section: Environmental Scanning Electron Microscopy (E-sem)mentioning
confidence: 99%
“…This technique is particularly well adapted for the observation or experimentation on biological samples (Muscariello et al, 2005). Images of small and highly hydrated samples such as liposomes have been obtained by several authors (Perrie et al, 2007 ;Ruozi et al;) without any particular sample preparation.…”
Section: Biology and Soft Matter Applicationsmentioning
confidence: 99%
“…A second report showed that it is possible to view unfixed, fully hydrated and uncoated cells with no dehydration effects for extended periods (in some cases even hours) but the user must have good knowledge of their sample. The osmotic pressure and rate of water loss from the specimen needs to be known to achieve this task [75,92].…”
Section: Advances In Sample Preparation Techniquesmentioning
confidence: 99%